A society of sorrow: the constitution of society through grief. Issue 2 (4th May 2019) - Brinkmann, Svend
ABSTRACT: In the sociology of the emotions, it has been common to approach emotions as socially constructed. Researchers have rightly asked how society and social processes shape emotional life, and this approach has generated many valuable insights. In this article, I argue that we should also approach the relation between emotions and society from a complementary perspective and ask how society itself is constituted through specific emotional processes. Social researchers of existential leanings have argued along these lines, pointing out how the human fear of death is crucial for the constitution of society. I argue that an equally fundamental emotion for the constitution of society is grief. I take up Tony Walter's claim that grief underlies the very constitution of society and seek to develop it into a broader understanding of how human social life presuppose practices of grief and mourning, which enable collectives to move into the future on the basis of their past. I end with a brief discussion of how the current pathologization of grief may impact societal processes and our views of human beings.